Translanguaging-Mediated Input, Response, and Feedback for a Positive Learning Environment (2023)
ABSTRACT : This action research aims to examine the influence of input, response, and feedback through translanguaging on one EFL classroom environment. It was developed in a rural public school in Rionegro, Antioquia with 32 tenth graders. The study examines IRF teacher-student interactions, with a focus on feedback, and their influence on students' confidence, motivation, and willingness to actively participate, engage, and learn English in a positive learning environment. Data were collected through participant observation, audio recordings of classes, 4 individual and 1 focus group interviews, questionnaires. After qualitative analysis of classroom interactions, the results show that translanguaging made the classroom environment more communicative. Students used English and Spanish to participate and communicate. Positive feedback raised students’ interest and involvement. The role of the teacher was found to have great impact on generating a positive learning environment.